Complete Genome Sequence of Clostridium acetobutylicum DSM 1731, a Solvent-Producing Strain with Multireplicon Genome Architecture - Bao, Guanhui (American Society for Microbiology, 2011)

(untitled)
Clostridium acetobutylicum is an important microorganism for solvent production. We report the complete genome sequence of C. acetobutylicum DSM 1731, a genome with multireplicon architecture. Comparison with the sequenced type strain C. acetobutylicum ATCC 824, the genome of strain DSM1731 harbors a 1.7-kb insertion and a novel 11.1-kb plasmid, which might have been acquired during evolution.